Accurate Nitrogen and Water Deficit Trigger Flavonoid and Proline Accumulation in Celery (Apium graveolens L.): Nitrogen dan Kekurangan Air Meningkatkan Akumulasi Flavonoid dan Prolin pada Seledri (Apium graveolens L.) - Kurniawan, Andi; Udayana, Cicik; Meiana M, Nadya Inri; Salsabila, Salvia; Barunawati, Nunun (Jurnal Ecosolum, 2024)
Celery is a plant that produces secondary metabolites, known as flavonoids, with distinctive taste and smell. Flavonoids are synthesized in leaves and mainly accumulate in vacuoles of cells. Water deficit is one of the abiotic stress factors that affect the increase of several amino acids as cofactors that form secondary metabolites. Moreover, nitrogen nutrients have an essential role in the formation of amino acids and chlorophyll. The research results show that the total fresh weight increased at around 450 g by applying 200 kg N ha-1 under 100% field capacity (FC). Consequently, there was an increase in fresh weight, followed by the biomass of celery, which was 1/15 of fresh weight. Meanwhile, the accumulated flavonoid concentration was higher at 50% field capacity and 100 kg N ha-1. Surprisingly, the content of proline and flavonoids in leaves of the same age had higher concentrations at 100 kg N ha-1 and 50% FC compared to the concentration of proline and flavonoids at 200 kg N ha-1 in the form of urea fertilizer, namely 0.25 µmol g-1 and 67.84 ppm, respectively. At 50% FC and 100 kg N ha-1, it is slightly higher on proline and flavonoids than the application of 100% FC and 200 kg N ha-1. The highest accumulation of phosphorus in leaves is interestingly at around 0.51 ppm at 50% FC, compared to the application of 100% FC at 100 and 200 kg N ha-1 half bellows at around 0.3.